Effectiveness of alcohol treatment interventions integrated into routine tuberculosis care in Tomsk, Russia. (13th May 2013) - Shin, Sonya; Livchits, Viktoria; Connery, Hilary Smith; Shields, Alan; Yanov, Sergei; Yanova, Galina; Fitzmaurice, Garrett M.; Nelson, Adrianne K.; Greenfield, Shelly F.; ,
Abstract Aims To test the feasibility and effectiveness of brief counseling intervention (BCI) and naltrexone integrated into tuberculosis (TB) care in Tomsk, Russia. Design Using a factorial randomized controlled trial design, patients were randomized into: naltrexone (NTX), brief behavioral compliance enhancement therapy (BBCET), treatment as usual (TAU) and BCI. Setting and participants In the Tomsk Oblast, hospitalized TB patients diagnosed with alcohol use disorders (AUDs) by the DSM‐IV were referred at the start of TB treatment. Of the 196 participants, the mean age was 41 years and 82% were male. Severe TB (84.7% had cavitary disease) and smoking (92.9%) were common. The majority had a diagnosis of an AUD (63.0%); 27.6% reported nearly daily drinking and consumed a median of 16 standard drinks per day. Measurements Primary outcomes were 'favorable' TB outcome (cured, completed treatment) and change in mean number of abstinent days in the last month of study compared with baseline. Change in mean number of heavy drinking days, defined as four drinks per day and five drinks per day for women and men, respectively, and TB adherence, measured as percentage of doses taken as prescribed under direct observation, were secondary outcomes. Analysis based on 'intention‐to‐treat' was performed for multivariable analysis. Findings Primary TB and alcohol end‐points between naltrexone and no‐naltrexone or BCI and no‐BCI groups did not differ significantly. TB treatment adherence and change in number of heavy drinking days also did not differ significantly among treatment arms. Among individuals with a prior quitting attempt (n = 111), naltrexone use was associated with an increased likelihood of favorable TB outcomes (92.3% versus 75.9%, P = 0.02). Conclusions In Tomsk Oblast, Russia, tuberculosis patients with severe alcohol use disorders who were not seeking alcohol treatment did not respond to naltrexone or behavioral counselling integrated into tuberculosis care; however, those patients with past attempts to quit drinking had improved tuberculosis outcomes.